Optimization of Radio Frequency Sputtering of Graphite on Nitinol (Journal of University of Babylon for Engineering Sciences, 2021)
The unique performance offerings of Ni-Ti alloys which involve the shape memory effect, super elasticity and biocompatibility have led to widespread acceptance of these alloys as valuable engineering materials. Deposition thin film from graphite target on nitinol  by using radio frequency sputtering as physical vapor deposition method . Determination  the improvement in hardness, wear rate, roughness, corrosion rate and cell viability before and after deposition. Three values of  radio frequency sputtering as (200W, 400W, 600W) are used. The deposited film is considered as diamond like carbon DLC depending on peaks of Raman spectroscopy. DLC had good characteristics as antibacterial property, low friction coefficient, high wear resistance and good corrosion resistance. High power led to high Vickers hardness as 657 with low specific wear rate as 7.34*10-8g/cm. High corrosion resistance achieved after 400W as 0.001mm/y and high cell viability as 93.11%. The optimized results from genetic algorithm with fuzzy inference system pointed as power 222W, Vickers hardness as 666,corrosion current density 0.138,and cell viability as 88.8.